Profile of APSRTC-With Reference to Visakhapatnam City - Lydia, R.; Ravi Kumar, B.; Lakshmi, B. Vijaya (International Journal of Business and Management Future, 2018)
Transportation plays an important role in the modern society particularly RTC buses. For the continuous development of India there should be a synchronized transport system. Competitiveness and increasing productivity are based on the efficient transport system that exists in the country. Efficient transport is indispensable to the economic development of nation. There are various modes of transport that include road transport, rail transport etc. The present study is an endeavor to depict the empirical profile of APSRTC – Visakhapatnam City.